2009
DOI: 10.1016/j.cej.2009.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Industrial wastewater treatment using hydrodynamic cavitation and heterogeneous advanced Fenton processing

Abstract: a b s t r a c tA combination of hydrodynamic cavitation and heterogeneous advanced Fenton process (AFP) based on the use of zero valent iron as the catalyst has been investigated for the treatment of real industrial wastewater. The effect of various operating parameters such as inlet pressure, temperature, and the presence of copper windings on the extent of mineralization as measured by total organic carbon (TOC) content have been studied with the aim of maximizing the extent of degradation. It has been obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(67 citation statements)
references
References 36 publications
2
60
0
5
Order By: Relevance
“…A number of studies reported application of hydrodynamic cavitation in wastewater treatment more specifically using conventional devices such as orifice and sparsely using nonconventional types such as vortex diode [2,3,[5][6][7]. However, most of the reported literature focuses on applications such as removal of dyes or for disinfection and systematic studies on solvent degradation, especially using hydrodynamic cavitation (both linear and vortex flow) have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies reported application of hydrodynamic cavitation in wastewater treatment more specifically using conventional devices such as orifice and sparsely using nonconventional types such as vortex diode [2,3,[5][6][7]. However, most of the reported literature focuses on applications such as removal of dyes or for disinfection and systematic studies on solvent degradation, especially using hydrodynamic cavitation (both linear and vortex flow) have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…One of the known methods of intensification of processes involving solid phase reagents is the application of acoustic oscillations, in particular in the ultrasonic range [9]. Therefore, further studies were aimed at establishing efficiency of application of ultrasound radiation in the processes of wastewater treatment with calcium hydroxide.…”
Section: Discussion Of Results Of Examining the Technology Of Wastewamentioning
confidence: 99%
“…Therefore, we studied the effect of calcium compounds, in particular calcium hydroxide, which is a cheap reagent of natural origin, on formation of sediment and the magnitude of BCO. Since calcium hydroxide is characterized by very low solubility (1.5 g/dm 3 ), to intensify the process with its participation, we applied acoustic oscillations of the US-range [9]. Therefore, further studies were aimed at defining efficiency of application of ultrasonic radiation in the processes of wastewater treatment with calcium hydroxide.…”
Section: Results Of Examining the Technology Of Wastewater Treatment mentioning
confidence: 99%
“…Fenton process, consist of a mixture of ferrous ion and hydrogen peroxide generating hydroxyl radicals (OH•) at room temperature as described by Walling et al 15 . When Fenton reagents, Fe 2+ /H 2 O 2 , are coupled with ultrasound, active hydroxyl radicals will be generated 16 followings the sonochemistry reactions described below, which will to produce the intermediate complex (Fe-O In Fenton process, the rate of reaction between H 2 O 2 and Fe 2+ increases with an increase in temperature leading to formation of more number of hydroxyl radicals, which in turn results in enhanced degradation efficiency 17 . However, for higher amplitude ultrasound at pH > 4, the formation of Fe (II) complexes reduces the generation of free radicals and also regeneration of ferrous ion will gets inhibited by the precipitation of ferric oxyhydroxides 18 .…”
Section: Resultsmentioning
confidence: 99%